The Education and Training on Making Local Microorganisms (MOL) as Activators of Organic Fertilizer on a Household Scale in the Women's Farmer Group in Darmaji Village, Central Lombok Regency: Education and Training on Making Local Microorganisms (MOL) as Activators of Organic Fertilizer on a Household Scale in the Women's Farmer Group in Darmaji Village, Central Lombok Regency - Nurhidayah; Hijriati Sholehah; Nefi Andriana Fajri; Hairun Anwar; Sahril Ramadoan; Mulhidin (Universitas Mataram, 2024)
The northern part of Central Lombok Regency is a pristine area, one of which is Darmaji Village, with the majority of the population working as farm/plantation laborers and farmers/planters, as well as casual laborers. Generally, farmers use chemical fertilizers for plants on agricultural land and buy EM4 as a starter for making compost. From the problem of using chemical fertilizers and the constraints of the cost of purchasing EM4, a work program was created by utilizing surrounding waste or using leftover vegetables, rotten fruit and banana stems as basic ingredients for making MOL and organic fertilizer. The purpose of the service is to provide socialization, education and training to the KWT of Darmaji Village about MOL, organic fertilizer and how to make MOL, organic fertilizer by utilizing household waste. The benefits of this work program are that the Women Farmer Groups who attend can gain knowledge about MOL, organic fertilizer and how to make MOL and organic fertilizer by utilizing household waste that is easily available in the surrounding environment. The implementation time of this work program is October 2024 in Darmaji Village, Kopang District, Central Lombok Regency. The process of implementing the socialization began with the presentation of material on the definition of MOL, organic fertilizer, the impact of chemical fertilizers, the benefits of MOL and organic fertilizers, and the basic materials that can be used in making MOL and organic fertilizers. The target audience of the service is the Darmaji Village Women Farmers Group. This work program goes through two stages, namely the presentation of materials and then training. The results of this work program are MOL products, compost products and based on the evaluation of understanding, namely the MOL challenge before the activity, around 69% did not understand, 30% enough and 1% good, while after the activity around 60% were good, 30% understood enough, 10% did not understand. Organic Fertilizer before the activity 70% understood enough, 5% good and 25% less, after the activity 80% were good, 10% enough, 5% did not understand, based on the results of the evaluation, this activity is useful according to the needs of the Community. Keywords: Socialization, Education, Training in making MOL and organic fertilizer